Removing the sporoderm from the sporoderm-broken spores of Ganoderma lucidum improves the anticancer and immune-regulatory activity of the water-soluble polysaccharide - Fang, Liu; Zhao, Qian; Guo, Cuiling; Guo, Dandan; Li, Zhenhao; Xu, Jing; Guo, Chengjie; Sang, Tingting; Wang, Ying; Chen, Jiajun; Chen, Chaojie; Chen, Rong; et al. (Frontiers in Nutrition, 2022)
Plant-derived polysaccharides have demonstrated promising anti-cancer effects via immune-regulatory activity. The aim of the current study was to compare the chemical property and the anticancer effects of polysaccharides extracted from the sporoderm-removed spores of the medicinal mushroom Ganoderma lucidum (RSGLP), which removed the sporoderm completely, with polysaccharides extracted from the sporoderm-broken spores of G. lucidum (BSGLP). We found that RSGLP has a higher extraction yield than BSGLP. HPGPC and GC-MS results revealed that both RSGLP and BSGLP are heteropolysaccharides, but RSGLP had a higher molecular weight and a different ratio of monosaccharide composition than BSGLP. MTT and flow cytometry results demonstrated that RSGLP exhibited much higher dose-efficacy in inhibiting cell viability and inducing apoptosis than BSGLP in 8 cancer cell lines representing colon (HCT116 and HT29), liver (HepG2 and Huh-7), breast (MDA-MB-231 and MCF-7), and lung cancers (NCI-H460 and A549). Furthermore, RSGLP is more effective in inhibiting HCT116 and NCI-H460 xenograft tumor growth and inhibiting tumor-induced splenomegaly than BSGLP in nude mice, suggesting a better effect on regulating immunity of RSGLP. Next, we found that RSGLP is more potent in inhibiting the level of serum inflammatory cytokines in nude mice, and in inhibiting the activation of macrophage RAW264.7 and the expression of the inflammatory mediators IL-1β, TNF-α, iNOS, and COX-2 in vitro. This is the first study to compare the chemical properties, anti-cancer, and immune-regulatory effects of RSGLP and BSGLP using multiple cancer cell lines. Our results revealed that the sporoderm-removed spores of G. lucidum (RSGL) and RSGLP may serve as new anticancer agents for their promising immune-regulatory activity.